Control of polymer-packing orientation in thin films through chemical structure of D-A type polymers and its application in efficient photovoltaic devices. (15th September 2015) - Choi, Min-Hee; Ko, Eui Jin; Han, Yong Woon; Lee, Eui Jin; Moon, Doo Kyung
Abstract: Controlling solid-state order of π-conjugated polymers through macromolecular design is essential for achieving high electronic device performance. Our work investigates the various effects of polymer structure on solid-state packing, especially, regarding polymer-packing orientation (edge-on vs. face-on). Various number of thiophene-containing isoindigo polymers (P4TI, P4TI-3, P4TI-4, P6TI-3 and P6TI-4) are synthesized via Stille coupling reaction. Differences in side chain position and spacer length are attributed to variation in energy levels and polymer backbone curvature. The orientation of the obtained polymers in thin films is confirmed by XRD measurement. Polymers (P4TI, P6TI-4) with shoulder peaks in UV–vis spectra of solution and film exhibit crystalized domains. Planar polymers prefer face-on orientation and provide more efficient organic photovoltaic (OPV) devices. The polymer solar cells are fabricated through a solution process and compared power conversion efficiency (PCE). P6TI-4 shows PCE up to 3.5%, with a short-circuit current density of 7.2 mA/cm 2, an open-circuit voltage of 0.70 V, and a fill factor of 66%. Graphical abstract: Highlights: The DA-type polymer materials with different length of π units are modified molecular energy level. Polymer packing orientation of DA-type polymers in thin films changed by the difference length of spacers was investigated. Face-on orientation polymer, P6TI-4, shows PCE up to 3.5%, with a JSC of 7.2 mA/cm 2, a VOC of 0.70 V, and a FF of 66.0%.